Kewenangan Pengawasan Kotak Kosong Atau Kolom Tidak Bergambar Pada Pemilu Yang Ada Di Indonesia - Bhonto Adnan Wally (PSHPM Untag Semarang, 2025)
Elections in Indonesia present a unique phenomenon in the form of an empty box or a blank column on the ballot, particularly in regional head elections with a single candidate pair (paslon tunggal). This phenomenon poses challenges in terms of oversight, as the empty box does not represent any specific candidate but still holds equal rights in the electoral process. This study aims to analyze the authority of election supervisory bodies in ensuring fairness and integrity in elections involving the empty box. The results of the study indicate that oversight of the empty box has not been comprehensively regulated in the legislation, leading election supervisors to encounter technical and legal challenges. The discussion highlights the importance of strengthening regulations related to the supervision of the empty box, the role of public participation, and recommendations to enhance the transparency and accountability of the electoral process. This study contributes to the development of a more inclusive and democratic electoral governance system.